El Precedente Administrativo frente a la Declaratoria de Insubsistencia de funcionario Público a partir del año 2019 al 2021 con base a la Ley 1437 de 2011 (2022)
The content of this research work allows visualizing the Administrative Precedent, in its development under the context of the Declaration of Insubsistence of a Public Official, through the application of the Means of Control of Nullity and Restoration of Law, where its evolution will be identified during the period of 2019 until 2021. Its first chapter will describe the inclusion of the insubsistence of the public official in parallel with the normativity, jurisprudence and principles in the administration under Law 1437 of 2011 and the Constitution of 1991. Later, in the Second Chapter, the Precedent is mentioned, and its conceptualization, its background, among other aspects, is found to reflect its importance in Colombia under the current regulations. Giving way to the Third Chapter that will allow us to know the practice of these figures through the citation of jurisprudence consistent with the aforementioned concepts.